Evolution in Seismic Properties During Low and Intermediate Water Saturation: Competing Mechanisms During Water Imbibition?. Issue 9 (2nd May 2019) - Pimienta, L.; David, C.; Sarout, J.; Perrot, X.; Dautriat, J.; Barnes, C.
Abstract: Despite the efforts reported in the literature to explain contrasting experimental observations, the evolution of seismic attributes (velocity and attenuation) of rocks across the saturation range remains ill understood. In a comparative study, we monitored the evolution of ultrasonic P wave attributes in a porous sandstone subjected to two experiments of moisture adsorption and water spontaneous imbibition. Both experiments highlighted a significant (i.e., by 1 order of magnitude) and similar drop in P waves amplitudes, although the maximum saturations reached in each experiment is very different (i.e., about 2% vs. 70%). However, only moisture adsorption leads to a dramatic elastic softening (velocity reduction). This difference might be explained by the coupling between two competing physical mechanisms taking place during water imbibition, namely, elastic softening driven by water adsorption at the grain contact and elastic stiffening driven by full saturation of the grain contacts, at the ultrasonic frequency of the measurement. Key Points: Comparative study of seismic monitoring of rock in low (moisture) and intermediate (imbibition) saturation range Strong amplitude loss, very similar to moisture adsorption, but little and uncoupled velocity variations during spontaneous water imbibition Evidence for two competing effects of adsorption‐induced softening and frequency‐dependent stiffening during water imbibition